(untitled) (African Human Mobility Review, 2021)
In this paper, the problems of labour migrants in their destination areas will be investigated, owing to the need for a deeper understanding of their specific livelihood problems in these areas. Using a mixed method approach to data collection, 100 migrant traders in Agbogbloshie, in the south industrial area of Accra, were interviewed about their livelihood problems. The data analysed revealed that the majority of labour migrants were not formally educated and were primarily involved in the trading of consumables. Additionally, conflict, poverty, decline in agriculture productivity and unavailability of social amenities were important factors that influenced their north-south migration in Ghana. Furthermore, inability to access credit facilities, theft of migrant traders’ wares, discrimination against migrants, exploitation of migrants by market leaders and harassment by city authorities were some of the problems that migrant traders faced. Dependent on these findings, to effectively minimise these problems, it is suggested that migrant traders should unionise as this can help them access credit from formal financial institutions. It would also present migrants with a common voice to engage in dialogue with city authorities on the appropriate ways of managing their activities in the market.